Role of pressure and pore microstructure on seismic attenuation and dispersion of fluid-saturated rocks: laboratory experiments and theoretical modelling. Issue 3 (27th July 2022) - He, Yan-Xiao; Wang, Shangxu; Xi, Bo; Tang, Genyang; Yin, Hanjun; Zhao, Liming; Sun, Chao; Ma, Xiaoyi
SUMMARY: Understanding the effects of pressure and rock microstructure on seismic elastic properties of fully saturated rocks is of considerable importance in a range of geophysical applications, especially at seismic frequency range. A recently proposed theoretical model of squirt attenuation and dispersion can be used to interpret the stress and frequency dependence of elastic properties on the basis of a triple porosity structure. The poroelastic model requires the knowledge of a variety of pore microstructure parameters, in particular, the compliant pores with a discrete distribution of aspect ratio. We performed laboratory measurements of (compressional and shear wave) velocity dispersion and attenuation, associated with the pressure-related closure of compliant pores on three dry and wet sandstones, to verify the effects of squirt flow arising from compressibility heterogeneities in the rock microstructure on the pressure dependence of dynamic elastic moduli and attenuation. Ultrasonic velocities experimentally measured on dry rocks were applied to extract pressure-dependent pore aspect distribution of compliant pores and the effective porosity of three types of pores with distinct aspect ratios, via fitting of the poroelastic model to the pressure dependence of elastic compressibilities. Under the assumption of frequency-independent dry elastic properties, inferred velocities and the associated attenuation of the saturated rocks from the forced oscillation experiments, which are still scarcely investigated, are in fairly good agreement with the predictions of the squirt model of three porosity types at seismic frequencies. The Gassmann's relation was found, nevertheless, underpredicts the ultrasonic saturated velocity measurements. The results validate applicability of the recently developed squirt model to account for dispersion and attenuation of phase velocities at varying effective pressures.